Direct production of aviation fuels from microalgae lipids in water. (1st January 2015) - Fu, Jie; Yang, Cuiyue; Wu, Jianghua; Zhuang, Julia; Hou, Zhaoyin; Lu, Xiuyang
Highlights: Aviation fuels can be synthesized directly from microalgae lipids in water over Pt/C. Pt/C is capable for decarboxylation of all test model compounds of microalgae lipids. Pt/C keeps the catalytic activity on decarboxylation even at the third use. Mechanism of direct decarboxylation of fatty acid esters is proposed. Optimum reaction condition for decarboxylation of methyl stearate is obtained. Abstract: In this contribution, we confirmed that aviation fuels could be synthesized directly from microalgae lipids in water over a Pt/C catalyst without additional hydrogen. After decarboxylation at 330 and 370 °C for 120 min, the oxygen content in the microalgae lipids was significantly reduced and the heating value of produced aviation fuels was greatly increased. The reaction mechanism of direct decarboxylation of microalgae lipids to aviation fuels was further investigated using each of the representative compounds in microalgae lipids, such as methyl laurate, methyl eicosanoate, methyl stearate, ethyl stearate, and tristearin as the starting material in separate reactions under the same conditions. Those reaction conditions, solvent, water loading, catalyst loading and reactant loading, were optimized. It was concluded that among the tested solvents, water was the most favorable for the selective decarboxylation of methyl stearate, that the catalytic decarboxylation rate of fatty acid esters with larger carbon numbers in water was faster than those with smaller carbon numbers, and that the Pt/C catalyst retained its activity through its third use. These results provide new insights for the direct decarboxylation of microalgae lipids to aviation fuels.